Implementasi Model Dan Desain Pembelajaran Daring Pada Anak Usia Dini Saat Pandemi Covid 19 di TK Perwanida Sooko Ponorogo - Mustofa, Zamzam; Azizah, Dica Nurul; Fitriyah, Ruaidatul (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2021)
Early Childhood Education is education at an early stage, in early childhood, children learn from those who cannot until they can. Of course, to teach children, teachers who are able to educate children well. As a good educator, he must have a learning model or design to support the teacher when teaching children. With this the purpose of this research is written to find out how to model and design good learning for children. Moreover, during a pandemic like this, the teacher must choose the appropriate and suitable learning model and design for children while studying at home. By using descriptive methods we can find out how an educator applies models and designs for early childhood. This research results that learning models and designs are very important for early childhood. learning models and designs such as role models or guidelines used by educators when carrying out learning activities for early childhood at school. If educators do not have a learning model or design that is suitable for early childhood, the teachers / educators will be confused about what kind of learning is appropriate and suitable for early childhood. As well as learning models and designs that are appropriate to use during a pandemic like this is to create a sense of comfort and safety even though they continue to carry out learning activities at home. Teachers / educators must prepare effective and efficient work programs so that they can improve the skills and intelligence of their students when studying at home.